2003
DOI: 10.1159/000070563
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Amyotrophic Lateral Sclerosis in the Local Health District of Ferrara, Italy, 1964–1998

Abstract: One of the epidemiologic characteristics of amyotrophic lateral sclerosis (ALS) still under discussion is whether the incidence of ALS is increasing over time. We performed a new investigation expanding our previous study of ALS in the local health district (LHD) of Ferrara, northern Italy, to determine whether there have been any changes in the incidence of ALS in the years 1964–1998. We used a complete enumeration approach by reviewing all possible sources of case collection available in the study area. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…Long-term analyses have been retrospective in nature. Govoni et al 2 reported that the incidence of ALS in Italy between 1964 to 1998 increased from 1.07 to 2.19 per 100,000, but the authors suggested that this was likely a result of the aging of the population that occurred over this time period; the largest increase in incidence occurred in those over 65 years old, which directly corresponded to the large increase in population in that age group. In another long-term study, Sorenson et al 7 conducted a retrospective review of ALS cases over the years of 1925-1998 and found no increase in ALS incidence over this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term analyses have been retrospective in nature. Govoni et al 2 reported that the incidence of ALS in Italy between 1964 to 1998 increased from 1.07 to 2.19 per 100,000, but the authors suggested that this was likely a result of the aging of the population that occurred over this time period; the largest increase in incidence occurred in those over 65 years old, which directly corresponded to the large increase in population in that age group. In another long-term study, Sorenson et al 7 conducted a retrospective review of ALS cases over the years of 1925-1998 and found no increase in ALS incidence over this time.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Many of these studies analyzed large geographic areas with unstable populations, creating methodological challenges with respect to ABSTRACT: Objective: Previous studies have suggested that the incidence of amyotrophic lateral sclerosis (ALS) in Nova Scotia is relatively high and increasing over time. This study was performed to determine the current incidence of ALS in Nova Scotia and to compare this to data collected in 1984 and 1995.…”
mentioning
confidence: 99%
“…Differences in the geographic distribution of ALS have been suggested [7,13,19,20] , and some studies have found a greater incidence of ALS among whites than blacks or other races [17] , while other studies have failed to demonstrate a significant difference among racial groups [19] . An increase in both the number of cases and deaths from ALS has also been noted over the past few decades [7,14,[17][18][19][20] ; while this fi nding has been suggested to be due to a growing population of elderly persons, and thus an increase in the population at risk [20] , a true increase in the incidence rate of ALS cannot be excluded. Thus, certain features of the epidemiology of ALS remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 The incidence was higher in the elderly than in younger adults, showing that the SE risk is age-and sex-dependent in southern Europe too. 2,3,5,6 Although case underestimation by this study is unlikely, [9][10][11] in SE studies there may be several sources of underestimation, 3,17 so the current incidence should be regarded as a minimal SE incidence. 3 The other findings were also similar to those of other studies, 2,3,5,6 such as cerebrovascular disease being the main aetiology in both acute and remote symptomatic cases, a history of epilepsy being present in fewer than 50% of the incident patients, partial SE and partial secondarily generalised SE being the most common seizure types and the majority of SE cases lasting for less than 24 hours.…”
Section: International Healthmentioning
confidence: 71%